Pengeringan Bengkuang Dengan Sistem Pengeringan Beku Vakum (Vacuum Freeze Drying System) - S, Awal Januari; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
One of the areas in Riau Province which produce commodity of yam bean is Bukit Payung Village, District of Bangkinang Seberang. Endurance of fresh yam bean is not longer in time, marketing can not spread and low resale value. It required a technology of post-harvest processing to overcome these problems of yam bean. In this study conducted by preservation using vacuum freeze drying method. The amis of these studies are to produce a vacuum freeze drying machine of yam bean; dry yam bean to 90% moisture content lost; studied the effect of vacuum freeze drying process to  the  characteristics  of  vacuum freeze-drying.  The methods used in this research are design methods and experimental methods. Vacuum freeze drying machine of yam bean was successfully made according to the needs of vacuum freeze drying and in accordance with the draft. Based on the test results it can be concluded that the maximum content of water lost  62% is carried by the rapid freezing method. Based on the material  phase change  in  testing, the best method for  the sublimation process is  by kept temperature constant at -5oC. Keywords: vacuum freeze drying, moisture, temperatur, yam bean.